The Effect of Wittrock’s Model on the Achievement of Fifth Grade Literary Students in Philosophy and Psychology - lsmaeel, Hadeel lbraheem; khamees, Tariq Hashim (Journal of Tikrit University for Humanities, 2023)
Wittrock’s model provided the opportunity for students to interact with the educational content by moving directly between its various steps, making them the focus of the educational process, and eliminating classroom routine by creating a classroom atmosphere dominated by movement, activity, and interaction with the scientific material, and presenting and discussing various information and ideas taking into account that the traditional method lacks all of that. This model emphasizes the effectiveness of the teacher within the classroom and emphasizes the process of giving the learner as much information as possible. It also focusing upon emphasizing memorization without concern for the type of information and the learner’s ability to achieve meaningful learning by linking the new information with his previous experiences and recalling it at the time of need. This can be explained by the fact that the use of modern teaching models, especially the Wittrock model, helps to develop the power of observation and interpretations of phenomena, and to reach conclusions by modifying and facilitating the information, data, and facts that are presented in a way that is consistent with the nature of the study material, in addition to that it represents the backbone of studying, understanding and comprehending the subject of psychology.